The Effects of Varying Structured Physical Activity Duration on Young Children's and Parents' Activity Levels. Issue 4 (2nd October 2019) - Filanowski, Patrick M.; Iannotti, Ronald J.; Crouter, Scott E.; Vermeulen, Anne; Schmidt, Ellyn M.; Hoffman, Jessica A.; Castaneda-Sceppa, Carmen; Milliken, Laurie A.
ABSTRACT: Purpose : The purpose of this study was to examine whether structured physical activity (PA) in a family-based community exercise program affects PA of young children and parents. Method : Twenty-two children (mean ± SD; age, 4.9 ± 2.1 years) and their parents (age, 34.3 ± 7.6 years) participated in unstructured PA sessions followed by either short- or long-duration structured PA sessions, while wearing an ActiGraph GT9X activity monitor on their right hip to estimate PA. Independent t-tests compared children's and parents' PA during short- and long-structured PA sessions. Paired t-tests compared short- versus long-structured PA sessions. A mixed model ANOVA compared PA during unstructured versus structured sessions and between children and parents. Results : Children spent proportionately more time in moderate-to-vigorous PA (MVPA) and had higher accelerometer counts/min than parents during short-structured PA (children:60.9 ± 18.8% vs. parents:17.7 ± 6.8%, children:3870 ± 742 vs. parents:1836 ± 556 counts/min, p < .05) and long-structured PA (children:61.1 ± 20.1% vs. parents:12.6 ± 4.9%, children:3415 ± 758 vs. parents:1604 ± 633 counts/min, p < .05). No statistical differences were found between short- and long-structured PA sessions for proportion of time spent in MVPA or counts/min for children or parents (all, p > .05). Children spent proportionally more time in MVPA and had higher counts/min during unstructured PA compared to structured PA (unstructured MVPA:54.4 ± 3.9% vs. structured MVPA:38.2 ± 4.2%, unstructured counts/min:3830 ± 222 vs. structured counts/min:2768 ± 239 counts/min; p < .05). Conclusions : Children were more active than parents during both the unstructured and structured PA sessions. However, unstructured PA sessions resulted in 63–77% and 10–11% of PA recommendations for children and adults, respectively. Family-based exercise programming can provide an opportunity for children and their parents to attain MVPA during the week.